Train your brain puzzle book Level 3, For advanced puzzlers - British Mensa; Baxendale, Katie (London Carlton Kids, 2014)
Packed with tricky logic problems, this title features brain-busting puzzles that can keep you entertained for hours. It helps you stun your school friends and amaze your parents with your awesome brainpower as you work your way through these mind-twisting challenges
Games & Recreations
1 2 23
Keywords: Mathematical recreations -- Children's nonfiction; Mathematical recreations; Puzzles -- Children's nonfiction